Partnering with NGOs to Strengthen Management : An External Evaluation of the Chief Minister's Initiative on Primary Health Care in Rahim Yar Khan District, Punjab - World Bank (Washington, DC, 2014)
The Chief Minister's Initiative on Primary Health Care (CMIPHC) is an innovative effort in the Punjab province of Pakistan. It is aimed at improving the delivery of primary health care by strengthening the services provided in basic health units (BHUs). There are about 3,060 BHUs in the Punjab and in 2002 they saw only 22 patients per day (or about 0.33 visits per capita per year, which is quite low by global standards). In order to improve BHU services and restore the confidence of the community, the CIMPHC formed a partnership with a non-governmental organization (NGO). In March 2003, the District Government of Rahim Yar Khan signed a memorandum of understanding with the Punjab Rural Support Program (PRSP), handing over the management of all 104 BHUs in the district. PRSP introduced a number of innovations, including recruiting district managers on contract at market rates, forming clusters of three BHUs managed by a medical officer in charge whose salary was 150% higher than the government standard, and improving the physical condition of the BHUs. PRSP was provided with the same budget as had been allocated the year before to run the BHUs. From the start, the experience spurred considerable debate in Pakistan. Twelve districts in Punjab have now chosen to contract the management of their BHUs to PRSP. The President of Pakistan intends to expand this initiative to other parts of the country.